PENGARUH KOMPENSASI BERBASIS INSENTIF TERHADAP KINERJA MANAJERIAL DENGAN BIG FIVE PERSONALITY TRAITS SEBAGAI VARIABEL MODERASI - Dewinda, Mutty Claudia; R, Mandasari (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to test and provide empirical evidence of the effect of incentive-based compensation as extrinsic motivation on managerial performance. This study also used individual intrinsic motivation, namely the big five personality traits to test the moderating role affecting the relationship between incentive-based compensation and managerial performance. This quantitative research was conducted using a survey method of managers, with a total of 115 participants. The results showed that incentive-based compensation affects managerial performance. The big five personality traits, extraversion, and conscientiousness, significantly weakened the relationship between incentive-based compensation and managerial performance in this study. However, agreeableness and openness had no significant effect in weakening the relationship. Neuroticism also did not significantly strengthen the relationship between incentive-based compensation and managerial performance. Keywords: Incentive-based Compensation; Managerial Performance; Big Five Personality Traits